The Impact of Samsung Scandal in South Korean Corporate Culture: Is Corporate Governance Necessary? - Kholifatus Saadah (Global Strategis, 2017)
As one of the world’s poorest countries in the world 30 years ago, South Korea proved its remarkable economic development. Within three decades, South Korea’s economic development shot up and attracted international attention. The economic strength in South Korea is supported by several global corporations such as Samsung, LG, Hyundai and others. The corporations have South Korea’s “ala” power, chaebol. Chaebol itself is similar to keiretsu in Japan, which global corporations are run by families and are hereditary. As time goes by, South Korea with its corporate culture does provide many advantages for South Korea as a whole, but this condition does not last forever. Not on the decline in revenues to South Korea’s economy, but the scandal of some global corporations in South Korea, especially Samsung raises new questions, should the South Korean Corporate culture be changed in the future? This question will be answered and explained in this paper. The author will explain through the history of the Korean corporate culture that is influenced by Confucianism, Samsung’s history to become a global corporate power for South Korea as well as an analysis of corporate governance on the economic situation in South Korea.